2015
DOI: 10.1128/jvi.01448-15
|View full text |Cite
|
Sign up to set email alerts
|

The Fusion Protein Specificity of the Parainfluenza Virus Hemagglutinin-Neuraminidase Protein Is Not Solely Defined by the Primary Structure of Its Stalk Domain

Abstract: Virus-specific interaction between the attachment protein (HN) and the fusion protein (F) is prerequisite for the induction of membrane fusion by parainfluenza viruses. This HN-F interaction presumably is mediated by particular amino acids in the HN stalk domain and those in the F head domain. We found in the present study, however, that a simian virus 41 (SV41) F-specific chimeric HPIV2 HN protein, SCA, whose cytoplasmic, transmembrane, and stalk domains were derived from the SV41 HN protein, could not induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 31 publications
(51 reference statements)
1
14
0
Order By: Relevance
“…Alteration of the domain of residues 84 to 105 in NDV HN reduces both F interactions and fusion (28), with mutations to the specific HN residues 89, 90, and 94 producing decreased F interactions (32). A region in the PIV5/SV41/ human PIV2 (hPIV2) HN head also appears to play a role in keeping the HN stalk in a conformation favorable for F triggering though the head itself does not appear to be directly interacting with F (23,55). Additionally, complementation studies using MeV and canine distemper virus (CDV) showed that residues 110 to 114 in the MeV H stalk allow specificity for CDV F (56).…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of the domain of residues 84 to 105 in NDV HN reduces both F interactions and fusion (28), with mutations to the specific HN residues 89, 90, and 94 producing decreased F interactions (32). A region in the PIV5/SV41/ human PIV2 (hPIV2) HN head also appears to play a role in keeping the HN stalk in a conformation favorable for F triggering though the head itself does not appear to be directly interacting with F (23,55). Additionally, complementation studies using MeV and canine distemper virus (CDV) showed that residues 110 to 114 in the MeV H stalk allow specificity for CDV F (56).…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of the HN protein revealed that there was low amino acid sequence identity (33.4%) between the APMV-2 Yucaipa and NDV SG10 strains, the residues at position 89 and 94 of IR region were also different between Yucaipa and other four viruses, which could be a possible reason for the decline of the fusion activity and virulence of the recombinant virus rSG10-YuHN. It is also reported that the conformation of the HN stalk domain in other paramyxoviruses could influence the interaction of HN protein with F protein in the cell-cell fusion ( Tsurudome et al, 2015 ). Whether this notion is applicable to NDV HN proteins needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Since the headless HN proteins of PIV5, SV41, NDV, and MuV have been found to efficiently activate their cognate F proteins and induce extensive cell–cell fusion ( Bose et al, 2012 , 2014 ; Tsurudome et al, 2015 ), the HN stalk domain seems to harbor sufficient elements for interacting with the F protein and activating it. However, we have recently found that the primary structures of the HN stalk domains cannot explain the unidirectional substitutability among the rubulavirus HN proteins ( Tsurudome et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the headless HN proteins of PIV5, SV41, NDV, and MuV have been found to efficiently activate their cognate F proteins and induce extensive cell–cell fusion ( Bose et al, 2012 , 2014 ; Tsurudome et al, 2015 ), the HN stalk domain seems to harbor sufficient elements for interacting with the F protein and activating it. However, we have recently found that the primary structures of the HN stalk domains cannot explain the unidirectional substitutability among the rubulavirus HN proteins ( Tsurudome et al, 2015 ). We also found that replacement of specified amino acids at or around the dimer interfaces of the HN head domain remarkably modify the F protein specificity, suggesting that changes in the head domain structure somehow alter the conformation of the stalk domain, thereby converting the F protein specificity ( Tsurudome et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation